Analysis of A High Rise Building Frame with Bracing and Shear Links at the External Members Using Analysis Tool Staad : A Review - Chauhan, Megha; Malviya, Pratiksha; Kushwaha, Nitesh (International Journal of Scientific Research in Civil Engineering, 2019)
Vertical shear-links in characteristic bracing systems, not similar to one located in the structure and can be easily changed or modify therefore, after the seismic effects, considering that other frame elements will remain elastic, only the vertical shear-links should be change, and then frame structure can function normally. a X type bracing system will be designed and fit with high accuracy and a small change in its characteristics reduce the ductility without increasing the stiffness, but unlike knee brace, vertical shear-link can be easily designed and implemented. In this review paper I am elaboration the past research work done related to lateral load resisting members, seismic forces and high rise building analysis using STAAD. Pro.